Efek Sitotoksik Ekstrak Daun Ketapang (Terminalia catappa L.) Pada Sel Kanker Payudara T47D - Barinta Widaryanti; Nur Khikmah; Nunung Sulistyani (Jurnal Biologi Papua, 2016)
Cancer is the second cause of death in the world after heart disease. Cancer therapy using natural product was considered has no side effect. Secondary metabolites from ketapang (Terminalia cattapa L) leaves has a prospect for cancer therapy. The objective of this research was to determine the cytotoxical effect of ketapang leaves on T47D breast cancer cells. Ketapang leaves were macerated using chloroform, ethyl acetate and methanol. Cytotoxicity effect were determined using MTT Cell Viability Assay. The result showed that chloroform, ethyl acetate and methanol extract were not able to reduce cell viability of T47D cells. Key words: cancer, ketapang, T. cattapa, cytotoxic, T47D cells.